Consideration of existing rainwater harvesting system and its enhancement using membrane filtration and UV-irradiation. - Trần, Diệu Linh (2020)
To clear the situation of RWH around the world and compare between developing and developed countries. To clear the current situation of RWH and people's attitude in a peri-urban area in Hanoi, Vietnam. To clear the applicability of existing water treatment devises to RWH for reduction of pathogenic risk.